Política de mobilidade sustentável e inclusiva em Ribeirão preto, SP: uma análise do transporte público por ônibus - Barioni, André (2011)
Urban Mobility is an attribute associated with the city and reflects the ease of moving people and goods in the space. The purpose of this research is to study the Public Transportation (operated by bus) and Urban Mobility in Ribeirão Preto-SP-Brazil, with emphasis on the concept of Sustainable Urban Mobility, discussed and adopted by the Ministry of Cities, Brazil. The public policies of the mobility in vigor were analyzed to identify and evaluate the works that have been made and how it has been applied by the government of the municipality. For this analysis we investigated the process of urbanization and urban restructuring. We believe that not understanding the process of urbanization and urban dynamics make the understanding of the implementation of public policies on mobility impossible. Thus, we considered the urban planning and the tools and resources that the government has to intervene in the area and then proceeded to examine the Plano Diretor and its supplementary laws. The research began with the process of theoretical and methodological refinement, with the understanding of the concept of urban sustainability and social inclusion, in addition to theoretical knowledge about the object of study and defined area which is the municipality of Ribeirão Preto- SP. At the same time, we analysed the data acquired, in the City Hall and on websites of the government, system-related and public transport, but also on the characterization and distribution of the population and socioeconomic data required to understand urban dynamics. We used the empirical method: using field work with the questionnaire, which was answered by users of public transportation by bus, Ribeirão Preto. Apart from general questions to find out what is the assessment system, the questionnaire also addressed questions about urban mobility and other modes of transportation, and issues that will present us with some significant data on the situation of the municipality of Ribeirão Preto. Through these data, superimposed on others, such as the distribution of trade and services centers that generate traffic, you could map where flows occur with greater intensity and, thereby, to find alternatives based on inclusive and sustainable urban mobility and the public transportation, which currently has the system and its operation to be delayed toward the central area where the municipality has already stimulated by the Plano Diretor, encouraging the creation of subcenters. This study helps to strengthen the scientific research that is being made on the Geography of Transport in South America, as in North America, specifically in the United States but also in some European countries like England, Spain and Holland, the study of this area of the Geography dates from the fifties of the twentieth century, based on Geography Theoretical-Quantitative. The interest in Geography of Transport is now appropriate to the problems faced in urban centers with high population density, because the urban mobility in the geographic space interacts with other socio-economic, which contributes to the efficiency or otherwise of the city, mainly in the economic and with regard to quality of life and social inclusion. Thus begins the studies in this area, to understand the urban and regional restructuring in its dynamics and consolidation, noting the current standards required in the search for a sustainable city, as well as in understanding the mobility of people and goods in urban area, which has been integrating a few decades the largest concentration of people.